LGM ice extent and deglaciation history in the Gurktal and Lavantal Alps (eastern European Alps): first constraints from 10Be surface exposure dating of glacially polished quartz veins - Wölfler, Andreas; Hampel, Andrea; Dielforder, Armin; Hetzel, Ralf; Glotzbach, Christoph (New York, NY [u.a.] : Wiley, 2021)
Compared with the western European Alps, the ice extent during the Last Glacial Maximum (LGM) and the subsequent deglaciation history of the eastern Alps east of the Tauern Window remain less well constrained. Also, considerable discrepancies exist between the mapped LGM ice margin and the ice extent predicted by ice-sheet models. Here we present the first 10Be surface exposures ages from two regions east of the Tauern Window (the Gurktal and Lavantal Alps), which provide constraints on the LGM ice extent and the deglaciation history. Our results show that the deglaciation of the Gurktal Alps occurred between 16 and 14 ka, which agrees with the predictions from ice-sheet models. In contrast, the 10Be ages from the Lavantal Alps located farther east are either LGM in age or predate the LGM, indicating that these regions were ice free or only partially covered by LGM ice. This finding suggests that ice-sheet models may have overestimated the LGM ice extent in the easternmost Alps. In conclusion, our study highlights the need for more age data from the eastern Alps to refine the location of the LGM ice margin and the deglaciation history, which is also crucial for climate-evolution and postglacial-rebound models.